2019
DOI: 10.1002/ccd.28279
|View full text |Cite
|
Sign up to set email alerts
|

Update on the clinical impact of mild aortic regurgitation after transcatheter aortic valve implantation: Insights from the Japanese multicenter OCEAN‐TAVI registry

Abstract: ObjectivesThis study aimed to compare the clinical impact of mild postprocedural aortic regurgitation (post‐AR) to that of none‐trivial post‐AR after transcatheter aortic valve implantation (TAVI) and to identify the vulnerability factors to mild post‐AR.BackgroundModerate–severe post‐AR, associated with increased mortality, is an important issue. However, the clinical impact of mild post‐AR remains controversial.Methods and resultsWe analyzed data from 1,572 consecutive patients (1,026 of none‐trivial post‐AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Recently, some studies demonstrated that even mild AR is considered an adverse prognostic indicator. 23,24 This finding could be an important factor in selecting devices for patients with a small aortic annulus.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Recently, some studies demonstrated that even mild AR is considered an adverse prognostic indicator. 23,24 This finding could be an important factor in selecting devices for patients with a small aortic annulus.…”
Section: Discussionmentioning
confidence: 89%
“…Conversely, the AR after TAVR was controlled trivial or less in the Sapien 3 group than in the Evolut R (50.8 vs. 63.2%), because of the outer skirt to reduce AR and higher radial force that enhances the sealing of the valve into the native annulus. Recently, some studies demonstrated that even mild AR is considered an adverse prognostic indicator 23,24 . This finding could be an important factor in selecting devices for patients with a small aortic annulus.…”
Section: Discussionmentioning
confidence: 99%
“…This applies to patients whose primary indication for surgery is severe aortic stenosis. However, the study by Yoshijima et al, likewise shows the importance of postoperative AR as compared to preoperative AR as an important predictor of outcomes.…”
mentioning
confidence: 98%
“…Yoshijima et al studied 1,572 patients who were enrolled in the Optimized transCathEter vAlvular Intervention (OCEAN‐TAVI) registry from 2013 to 2016, which involved 14 collaborating hospitals in Japan. The prospective OCEAN‐TAVI trial compared the Sapien XT/S3 (Edwards Lifesciences, Irvine, California) and the Medtronic CoreValve System (Medtronic, Minneapolis, Minnesota) for the treatment of severe aortic stenosis.…”
mentioning
confidence: 99%
“…8 In addition, the importance of decreasing PVL after TAVI, even in a contemporary TAVI cohort, to reduce the incidence of rehospitalization due to heart failure has been demonstrated. 9 The latest version of TAVI devices, meticulous screening, and procedural modification may improve clinical outcomes. It is also important to understand that "low risk" does not necessarily means "young age".…”
mentioning
confidence: 99%